Analysis of porous polymer membranes using FEM software for sensing applications. (2020) - Prasad, Brijesh; Gariya, Narendra; Panwar, Varij; Patil, Pravin; Kumar, Pushpendra
Abstract: Soft polymer sensors are appreciated for applications of electronic devices, sensors, actuators, human health and for structural health monitoring. Polyvinylidene Fluoride has been mostly used by various researchers for development of sensing applications. The sensing behavior depends on the surface morphology which acts as receptors. The change due to strain and stress are important parameters to identify sensor applications as the minor change in shape can affect the performance of the sensor. In this work, we focus on analyzing the deformation and stress behavior of the porous membranes by developing the model of Polyvinylidene Fluoride using solid works and analyzing the results using ANSYS software. It has been observed during the study that the generation of pores up to a certain level enhances the deformation or strain however, the higher concentration of pores increases the stress concentration.